Comprehensive strength and flexural strength of oil palm shell lighweight aggregate concrete containing crushed cockle shell as partial sand replacement - Dick Carlos, Phillip (2014)
Cockle shell is a waste produced from cockle industry which dumped at landfill thus causing environmental pollution. In this thesis, crushed cockle shell has been used as partial replacement of sand in oil palm shell (UPS) lightweight aggregate concrete to determine the mechanical properties of UPS lightweight aggregate concrete. The amounts of sand replaced by crushed cockle shell are varies from 5, 10, 15 and 20%. The tests conducted on concrete samples are compressive strength test and flexural strength test. All specimens were prepared and subjected to water curing until the testing date. The result shows that the use of cockle shell as partial sand replacement increase the compressive strength and flexural strength of OPS lightweight aggregate concrete.